THE EFFECTIVENESS OF EDUCAPLAY ACTIVITIES TOWARDS STUDENTS’ VOCABULARY MASTERY AT SMPN 25 BENGKULU CITY - Siti Nurkhasanah; Ferri Susanto; Yashori Revola (STKIP Subang, 2026)
This study aims to examine the effectiveness of Educaplay in improving vocabulary mastery of seventh-grade students at SMPN 25 Kota Bengkulu. The background of this research is the low vocabulary mastery of students due to conventional and monotonous teaching methods and the minimal use of interactive learning media. This study employed a quantitative approach with a quasi-experimental design (nonequivalent control group design). The population consisted of all seventh-grade students, with a sample of two classes: 26 students in the experimental class and 26 students in the control class. The research procedures included a pre-test, treatment for the experimental class using Educaplay for four meetings, conventional instruction for the control class, and a post-test. Data were analyzed using statistical tests with the assistance of SPSS version 27. The results showed a significant improvement in the experimental class compared to the control class, with the mean score increasing from 55.8 to 79.1 in the experimental class and from 49.7 to 66.8 in the control class. The independent t-test revealed t_calculated > t_table (4.596 > 2.009) with significance < 0.001, leading to the rejection of Ho and acceptance of Ha. The Partial Eta Squared value of 0.297 indicates that the use of Educaplay contributed 29.7% to the improvement of students’ vocabulary mastery. In conclusion, Educaplay has a significant effect on students’ vocabulary mastery. This media has the potential to serve as an innovative and effective interactive learning tool to enhance English vocabulary skills for junior high school students.